Peran Digital Storytelling dalam Promosi Pariwisata Kampung Adat Prai Ijing, Desa Wisata Tebara, Nusa Tenggara Timur - Liliana Dewi; Muammar Daffa Alfariz; Emanuel Jerubun (Bogor Hospitality Journal, 2026)
The purpose of this study is to identify the role of digital storytelling in promoting tourism in tha Prai Ijing traditional village. The research method used is a descriptive qualitative approach with data collection techniques through observation of tourism potential and social media and internet media of the Prai Ijing traditional village, interiews with the village head and the head of the tourism group, and literature studies related to the Prai Ijing traditional village and marketing strategies. The results of this study indicate that tourist attractions are in the form of cultural tourism, accessibility is quite easy to reach, amenities and accommodation are sufficiently available. The digital technology used is Instagram social media. Through the SOSTAC method analysis technique, it is known that the stages in SOSTAC have not been fully implemented to narrate the tourism potential of the Prai Ijing traditional village.